(untitled) - Whyte, R. O. (New York, 1974)
This study of the nutritional ecology of the rural Asians is designed to provide the essential background for those working, or preparing to work, on this fundamental aspect of rural life,...
Keywords: Diet,Nutrition,Food habits,Food supply,Ăn uống thường ngày; Asia,Asia,Asia,Châu Á